Analysis of the BGA solder Sn–3.0Ag–0.5Cu crack interface and a prediction of the fatigue life under tensile stress. (June 2016) - Chen, Yilong; Jia, Jianyuan; Fu, Hongzhi; Zeng, Zhi
Highlights: Fracture positions of the solder joint have been discussed using the interface colors. The tensile stress of the solder joints is inversely proportion to temperature. Thickness of the epoxy resin has great influence on solder joints tensile stress. Simulation results of the fatigue life of the solder joint agree well with the experimental results. The fatigue life of the solder joint is successfully predicted by the designed test machine. Abstract: In this work, the phenomena of solder joint fatigue fractures are researched. Both shear stress caused by thermal expansion and tensile stress caused by warpage can be the main factor that leads to the fatigue fracture of a solder joint. The fatigue fracture of BGA solder joints under tensile stress is discussed. Experiments were performed to illustrate the position of the BGA solder joint crack interface caused by tensile stress. The fracture interface will appear not only on the solder/Cu pad interface but also on the solder and Cu pad. Moreover, tensile stress and the fatigue life of BGA solder joints caused by warpage are simulated. Then, some significant conclusions are drawn by comparing the experimental results and simulation results. The experimental method can also be used for the other package types in the microelectronics industry.